A Model of Fuel and Energy Sector Contribution to Economic Growth - Polyakova, Aleksandra G.; Ramakrishna, Seeram A.; Kolmakov, Vladimir V.; Zavyalov, Dmitry V. (International Journal of Energy Economics and Policy, 2019)
The study examined the impact of foreign direct investment (FDI) in the fuel and energy sector and related industries on economic growth in response to the debates on FDI’s impact on economic growth being positive (government officials and policymakers) or negative (the World Bank, some researchers). The hypothesis that a significant relationship is present between the Russian Federation GDP and gross FDI in Fuel and Energy Sector (fuels and non-fuels fossils mining, coke and petrochemicals production, rubber and plastic production, and energy supply) is introduced and validated by using a regression model. The derived model tests changes of regression results patterns of the Russian GDP against FDI in energy-related industries in different periods 1998-2004 and 2010-2017. GDP is assessed in five different measures: current US dollars, international US dollars (purchasing power parity), growth rates of the former and the latter, and physical growth index. It was concluded that, to a greater extent, economic growth is influenced by foreign investment in energy supply and petrochemical production in the both periods. Increased investment in power generation also contributes to economic growth, while other constituents of the sector, including mining, have a statistically insignificant or even retarding effect on economic growth, thus evidencing in favor of the World Bank’s criticism towards FDI. Policy implications of the findings prove the necessity to introduce structural changes intended to redirect capital flows from oil and gas to prevent from economic growth deterioration in the long-term perspective. Keywords: Economic growth; Foreign Direct Investment; Fuel and energy sector JEL Classifications: C3, O4, Q43 DOI: https://doi.org/10.32479/ijeep.7849